Beyond stock stories and folktales African Americans' paths to STEM fields - Frierson, Henry T. 1944-; Tate, William; Lloyd-Jones, Brenda; Jean-Marie, Gaëtane (Diversity in higher education ;, 2011)
Historically, women of color have experienced discrimination based on the double jeopardy of race and/or ethnicity, and gender in their quest for access and advancement in higher education. Todays women of color in higher education however are the beneficiaries of courageous and committed women predecessors who confronted and disrupted institutions to attain a higher level of education (Jean-Marie, 2005). This two-edited volume focuses on African American, Hispanic American, Native American, and Asian-Pacific American women whose increased presence in senior level administrative and academic positions in higher education is transforming the political climate to be more inclusive of women of color. Topics include trends and issues, leadership styles/characteristics, tenure and promotion, mentoring/social networks, and challenges and opportunities. As a conceptual framework, the collection of chapters in the two volumes acquaints readers with a broad overview of the characteristics and experiences of women of color in higher education. The two volumes include: Women of Color in Higher Education: Turbulent Past, Promising Future, Women of Color in Higher Education: Contemporary Perspectives and Changing Directions.